Cultural Rituals for Young Children in Mongolia - Chuluun, Zayasuren; Batsaikhan, Javzandulam; Lkhagvadorj, Tsog-Erdene (Journal of Education Culture and Society, 2025)
Aim. The purpose of this work is to explore and thematically present the cultural rituals for newborns and young children and interpret the meaning of the ritual related to the Mongolian traditional way of life. In this article, we explore the origin, characteristics, development, symbols, and contributions of Mongolians to various rituals, such as blessing, bathing and naming newborns, first hair cutting ceremony, cutting fox shape with sheep wool felt, new dress blessing for young children, making trick to brown rabbit. Methods. The work is presented based on observations in daily life, secondary research documents, empirical materials, analysis of scientific research papers, and the use of the comparative method in the Mongolian cultural context. All of the rituals for young children presented in this paper are not only historical rituals but also commonly implemented in daily life, specifically in rural Mongolia. Results. These findings provide evidence of the continuity and importance of Mongolian rituals for newborn babies and young children, underscoring the enduring uniqueness of traditional Mongolian beliefs and practices for protecting, curing, and blessing. Despite the challenges of globalisation, Mongolian traditional rituals remain a valuable cultural expression, preserving their distinctiveness across generations. Conclusion. The rituals reflect the deeply spiritual and symbolic relationship that Mongolians have with the natural and supernatural world, as well as their commitment to protecting the emotional and physical well-being of their young children through cultural rituals.